2022
DOI: 10.1002/chem.202200344
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Influence of Diverse Secondary Metal Cations on Redox‐Active Palladium Complexes

Abstract: Incorporation of redox-inactive metals into redoxactive complexes and catalysts attracts attention for engendering new reactivity modes, but this strategy has not been extensively investigated beyond the first-row of the transition metals. Here, the isolation and characterization of the first series of heterobimetallic complexes of palladium with mono-, di-, and tri-valent redox-inactive metal ions are reported. A Reinhoudt-type heteroditopic ligand with a salenderived [N 2 ,O 2 ] binding site for Pd and a cro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 16 publications
(57 citation statements)
references
References 82 publications
(61 reference statements)
5
50
2
Order By: Relevance
“…The complexes behave as monomers in solution at 23 °C, as indicated by the solution state Evans method magnetic moment measurements, and 19 F NMR in CD 3 CN shows that the triflate anion dissociates in solution (see SI). The vanadium­(V/IV) redox event for V-Na, V-K, and V-Ba is reversible and shifts anodically with an increase in the cation charge, consistent with the effect on other heterobimetallic complexes in this ligand framework. , , Computational studies were also performed, and the same trend is observed, though the simple model used in the calculations overestimates the increase in E 1/2 as the cation charge increases (see SI for computational details and Table S3 for values). The vanadium­(V/IV) reduction potential for the monocations (V-Na and V-K) shifts 90–130 mV more positive than (salen)­V­(O) and 114–164 mV more positive than (salen-OMe)­V­(O).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…The complexes behave as monomers in solution at 23 °C, as indicated by the solution state Evans method magnetic moment measurements, and 19 F NMR in CD 3 CN shows that the triflate anion dissociates in solution (see SI). The vanadium­(V/IV) redox event for V-Na, V-K, and V-Ba is reversible and shifts anodically with an increase in the cation charge, consistent with the effect on other heterobimetallic complexes in this ligand framework. , , Computational studies were also performed, and the same trend is observed, though the simple model used in the calculations overestimates the increase in E 1/2 as the cation charge increases (see SI for computational details and Table S3 for values). The vanadium­(V/IV) reduction potential for the monocations (V-Na and V-K) shifts 90–130 mV more positive than (salen)­V­(O) and 114–164 mV more positive than (salen-OMe)­V­(O).…”
Section: Resultssupporting
confidence: 56%
“…Further, it is important to understand solvent effects on the redox properties, as it may determine reactivity profiles and stability of the vanadyl ion. Proximal nonredox active Lewis acidic metals are known to shift redox potentials and enhance reactivity. Increasing the magnitude of charge of a positively charged ion or substituent typically results in an anodic shift (positive shift) of reduction potential. Investigations on charge effects on homogeneous transition metal complexes are important for understanding electron transfer processes, spectroscopic properties, and impact on catalytic activity. Given the reversibility of the vanadyl (V/IV) redox couple and its role in reactions involving vanadium salen complexes, we investigated vanadyl salen-crown complexes containing various nonredox active cations to modify the redox properties (Chart ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, less Lewis acidic cations such as Zn 2+ and Ca 2+ did not result in changes to the UV–visible absorption profile of the Mn­(V) oxo system. In our own prior work with a family of heterobimetallic palladium complexes, systematic shifts in a CT transition were observed across a family of seven cations, including K + , Ca 2+ , and Lu 3+ . These observations underscore the important role of the crown-ether-like site in our macrocyclic ligand, which was used in both the work with palladium and the work here with vanadyl.…”
Section: Resultsmentioning
confidence: 64%
“…The 1 H NMR spectrum of [VO] features a distinctive but rather broad set of resonances (see the SI, Figure S1). The chemical shift values of the resonances for both the aromatic and aliphatic protons of our macrocyclic ligand are shifted from where they would be anticipated to be in diamagnetic complexes, in line with the paramagnetic nature of [VO] . However, elemental analysis results and structural data from X-ray diffraction (XRD) analysis confirmed the desired formulation of [VO] , including the presence of the free crown-ether-like [ O 6 ] site that appears poised for binding of secondary metal cations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation